Multiple Solutions of a Nonlocal Problem with Nonlinear Boundary Conditions - Jie Liu; Qing Miao (Discrete Dynamics in Nature and Society)
In this article, we consider a class of nonlocal p(x)-Laplace equations with nonlinear boundary conditions. When the nonlinear boundary involves critical exponents, using the concentration compactness principle, mountain pass lemma, and fountain theorem, we can prove the existence and multiplicity of solutions.